SUSPENDING THE ACTION OF LABOUR AGREEMENT DURING THE PERIOD OF MARTIAL LAW IN UKRAINE - Kmetyk, Khrystyna; Tyubay, Anastasia (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
The purpose of the article is to study a concept and a procedure for suspending the action of labour agreement during the period of martial law in Ukraine. Research methods: the method of comparative and documentary analysis, as well as the method of documentary synthesis and generalization. Together with the methods of objective truth and the cognitive-analytical method, a conclusion on the peculiarities of legal regulation of labour relations during the period of martial law in Ukraine is formulated. Results: the key differences between termination of labour relations by terminating the action of labour agreement, a downtime and suspending the action of labour agreement during the period of martial law in Ukraine were characterized and revealed. Discussion: the provisions of the Law of Ukraine “On Organization of Labour Relations under the Conditions of Martial Law” N 2136-IX dated March 15, 2022, which at present occupies a key position in the sphere of regulation of suspending the action of labour agreement during martial law in Ukraine, were reviewed and analysed, as well as practice of the Supreme Court of Ukraine on this issue.